1997
DOI: 10.1002/(sici)1096-9896(199701)181:1<14::aid-path730>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

DISTINCT mdm2/p53 EXPRESSION PATTERNS IN LIPOSARCOMA SUBGROUPS: IMPLICATIONS FOR DIFFERENT PATHOGENETIC MECHANISMS

Abstract: Recent findings have indicated that TP53 inactivation in sarcomas may result from mutation and/or deletion of the TP53 gene or, alternatively, from binding to the MDM2 gene products. To investigate further a possible role of the two genes in sarcomas, 24 large and deep‐seated lipomas and 74 liposarcomas of various subtypes were analysed for mdm2 and p53 overexpression by immunocytochemistry. Nineteen cases of the same series were also molecularly analysed for both MDM2 gene amplification and TP53 mutations, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
75
2
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(82 citation statements)
references
References 23 publications
2
75
2
1
Order By: Relevance
“…In our previous immunohistochemical and molecular investigations on liposarcomas, 21 we disclosed the existence of a particular subgroup that displayed a phenotype characterized by an overexpression of both mdm2 and p53 proteins associated with MDM2 gene amplification and by the absence of TP53 gene mutations. These findings led to the hypothesis that mdm2 sequestration of p53 could represent the mechanism leading to loss of p53 functions in this liposarcoma group, but the persistence of p53 gene product, demonstrated to be physically bound to mdm2, 16,22,23 strongly suggests that the latter could be defective in promoting the p53 degradation reported in other situations.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In our previous immunohistochemical and molecular investigations on liposarcomas, 21 we disclosed the existence of a particular subgroup that displayed a phenotype characterized by an overexpression of both mdm2 and p53 proteins associated with MDM2 gene amplification and by the absence of TP53 gene mutations. These findings led to the hypothesis that mdm2 sequestration of p53 could represent the mechanism leading to loss of p53 functions in this liposarcoma group, but the persistence of p53 gene product, demonstrated to be physically bound to mdm2, 16,22,23 strongly suggests that the latter could be defective in promoting the p53 degradation reported in other situations.…”
mentioning
confidence: 86%
“…All the cases included in our study were investigated for mdm2 amplification following the same protocol described by Pilotti et al 21 …”
Section: Southern Blotmentioning
confidence: 99%
“…These molecular events are consistently identified in these tumors and represent the main driver event. [6][7][8] To date, the role of these molecular abnormalities as predictive biomarkers for tumor behavior and prognosis has been explored in only a limited number of dedifferentiated liposarcoma cases. 9 The purpose of our study was to determine whether there are biomarkers that can be combined with morphological parameters to begin developing a risk stratification system or molecular grading system for dedifferentiated liposarcoma.…”
mentioning
confidence: 99%
“…Overexpression of the proteins including MDM2 and CDK4, which are encoded by the genes located in the 12q13-15 region, is well described in liposarcoma, and dedifferentiated components exhibit a high level of MDM2-positive inmmunoreactivity in dedifferentiated liposarcomas. 3,4 Hostein et al investigated the amplification level of MDM2 and CDK4 using quantitative real-time PCR, and higher-level amplification was observed in dedifferentiated liposarcomas than in well-differentiated liposarcomas. 27 Other than these genes, Sakamoto et al suggested that alteration of the b-catenin and H-ras gene is involved in the dedifferentiation in dedifferentiated liposarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Dedifferentiation is mostly considered a time-dependent phenomenon, and several reports have suggested an association between dedifferentiation and the altered expression of specific proteins, such as MDM2, P53, H-ras, b-catenin, and retinoblastoma protein (pRB). [3][4][5][6][7] pRB negatively regulates the cellular G1/S transition of the proliferative cell cycle and is required for proper differentiation of certain cell types, including skeletal muscle and adipocytes. 8 Decreased expression of pRB in malignant mesenchymal tumors has been reported by some authors based on immunohistochemistry or Western blotting.…”
mentioning
confidence: 99%